-20-6r=-4(2r+3)

Simple and best practice solution for -20-6r=-4(2r+3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -20-6r=-4(2r+3) equation:


Simplifying
-20 + -6r = -4(2r + 3)

Reorder the terms:
-20 + -6r = -4(3 + 2r)
-20 + -6r = (3 * -4 + 2r * -4)
-20 + -6r = (-12 + -8r)

Solving
-20 + -6r = -12 + -8r

Solving for variable 'r'.

Move all terms containing r to the left, all other terms to the right.

Add '8r' to each side of the equation.
-20 + -6r + 8r = -12 + -8r + 8r

Combine like terms: -6r + 8r = 2r
-20 + 2r = -12 + -8r + 8r

Combine like terms: -8r + 8r = 0
-20 + 2r = -12 + 0
-20 + 2r = -12

Add '20' to each side of the equation.
-20 + 20 + 2r = -12 + 20

Combine like terms: -20 + 20 = 0
0 + 2r = -12 + 20
2r = -12 + 20

Combine like terms: -12 + 20 = 8
2r = 8

Divide each side by '2'.
r = 4

Simplifying
r = 4

See similar equations:

| t^2+6-20=0 | | 3[f(4)(4)+1]= | | -x-29=11+4x | | 3x=5(16) | | f(x)=0x^0 | | 3x*x=147 | | 14-2+11+3= | | 5x+15=8x+2 | | 2(d+3)=28 | | f(x)=2x^1+0x^0 | | 15+5z=-10 | | -24-4x=15-x | | 3(m+1)=13 | | f/x | | 2[x-3(0)]= | | 3(5x-2)=4(2x+6) | | 10(c+7)=90 | | -8y+9=13 | | -7(2f+8)=-126 | | f(x)=3x^2+2x^1+0x^0 | | X=(20-2x)*(40-2x) | | 14n+2=72 | | 10(s-5)=-98 | | x=(20-2x)(40-2x) | | f(x)=2senx | | x^4+x^3-8x^2+16x+6=0 | | 225=x^2-16x+68 | | 0=y^2-4y-1 | | 3(3s+6)=72 | | 29+5y-2=15y-13-2y | | x+2x+1+8x-1+3x+2=58 | | 5(t-6)=5 |

Equations solver categories